THE EFFECT OF ENVIRONMENTAL COSTS, THE FOREIGN OF OWNERSHIP AND THE SIZE OF COMPANY ON RETURN ON ASSETS & CORPORATE SOCIAL RESPONSIBILITY AS INTERVENING VARIABLE - Haugesti Diana; Mimelientesa Irman (Journal of Applied Business and Technology, 2021)
This objective of this study was to determine the effect of the environment, foreign ownership of company size, and corporate social responsibility (CSR) on performance (ROA), and to find out whether environmental costs, foreign ownership, and company size on company performance (ROA) through corporate social responsibility (CSR) as Intervening variables. This research was included in the comparative causal research. The population of this study were mining companies listed on the Indonesia Stock Exchange in 2016-2019. Using purposive sampling method, there were 40 companies that meet the criteria with a total was160 data. The data analysis technique used was multiple linear regression analysis using SmartPLS software. The results of this study indicate that the variables of environmental costs, the foreign ownership, the size of company and the corporate of social responsibility there was no the direct or indirect effect on ROA.